Fabrication of Sr0.5Ba0.5Nb2O6 Nanocrystallite‐Precipitated Transparent Phosphate Glass‐Ceramics. Issue 11 (27th August 2013) - Masai, Hirokazu; Shirai, Ryota; Miyazaki, Takamichi; Yoshida, Kazuki; Fujiwara, Takumi; Tokuda, Yomei; Yoko, Toshinobu
Abstract : Transparent (Sr0.5 Ba0.5 )Nb2 O6 (SBN50) nanocrystallite‐precipitated phosphate glass‐ceramics were prepared by a conventional glass‐ceramic process. x (SrO–BaO–2Nb2 O5 ) − (100–4 x )P2 O5 ( x SBNP) glasses with a refractive index of 1.9–2.0 exhibited high water resistance owing to the presence of Q 0 and Q 1 phosphate units. Both bulk and surface crystallization of the SBN50 phase were observed in 20SBNP and 21SBNP glass‐ceramics. Although the nominal content of SBN50 crystals in the 21SBNP glass was larger than that in the 20SBNP glass, the latter exhibited better crystallinity of SBN50 and a higher number density of precipitated SBN nanocrystallites. By tuning the two‐step heat‐treatment and the chemical composition, transparent SBN50‐precipitated glass‐ceramics were successfully obtained. Given that no remarkable increase of the relative dielectric constants was observed after crystallization of the SBN50 nanocrystallites, it is postulated that the relative dielectric constant of the bulk is mainly governed by the amorphous phosphate region, and that the contribution of precipitation of the SBN50 nanocrystallites to the dielectric constant is not very significant in this system.